Religious coping as a determinant of psychological distress among married co-habiting Malaysians during the covid-19 pandemic - Chu Sin Yee; Siau Ching Sin; Chua Bee Seok; Mimi Fitriana; Rahmattullah Khan; Low Wah Yun (Fakulti Psikologi dan Pendidikan, 2021)
The COVID-19 pandemic resulted in the enactment of the Movement Control Order (MCO) in Malaysia on 18 March 2020, leading to drastic changes in family life. This study aimed to examine the influence of religion and religious coping on the psychological distress of Malaysian couples during the earlier stage of the COVID-19 pandemic. Between April and June 2020, we collected data using an online survey platform through snowball sampling to Malaysians who were married or cohabiting. Those who agreed to participate answered the Brief Religious Coping Scale and the Depression Anxiety and Stress-21. Most of the participants (N=199) were female (74.4%), 30 to 34 years old (21.5%), and Muslims (47.9%). Mean scores of positive and negative religiosity copings were 22.6 (SD = 6.03) and 11.0 (SD = 4.00) respectively. The results of three multiple linear regression models were significant for depression (R2=.25, F (8, 198) = 8.007, p<.001), anxiety (R2=.30, F (8, 198) = 9.949, p<.001), and stress (R2=.27, F (8, 198) = 8.415, p<.001). Positive religious coping was negatively associated with depression (β=-.36, p<.001), anxiety (β=-.41, p<.001), and stress (β=-.40, p<.001) after adjusting for demographic characteristics. Contrarily, negative religious coping was associated with higher depression (β=-.29, p<.001), anxiety (β=-.26, p<.001), and stress (β=-.27, p<.001) levels. The results suggest that positive religious coping such as focusing on religion to stop worrying and believing that God’s tests are strengthening the individual can be a protective factor against psychological distress among Malaysian couples. Vice versa, wondering if God is powerless or feeling punished by God was associated with worse psychological distress. This study indicated that religion remains an important consideration in psychological distress, and religious authorities and leaders may play a larger role in ameliorating the distress felt by individuals through strengthening their positive religious coping.